2017
DOI: 10.1002/hpm.2404
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mobile phone short message service on maternal health in south‐west Nigeria

Abstract: The SMS-based intervention has a positive effect on facility delivery, and mothers welcome its use in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 20 publications
1
19
0
5
Order By: Relevance
“…Around one‐third of the trials described efforts to address this problem in some way, for instance by offering vouchers to participants (e.g. Lund 2012; Omole 2018), or by offering participants free access to various internet sites in return for receiving mobile advertising (Gold 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Around one‐third of the trials described efforts to address this problem in some way, for instance by offering vouchers to participants (e.g. Lund 2012; Omole 2018), or by offering participants free access to various internet sites in return for receiving mobile advertising (Gold 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The versatility of mobile apps makes users more participatory, thus empowering them in making an informed choice for themselves 9. Using a mobile app as a tool for patient health management has become an extended healthcare service provided by hospital organizations 10–12. Hence, understanding technology acceptance from a patient’s perspective will enable hospital administrators or health care professionals to better design patient app content.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps is one of the healthcare services that has promotes patients’ health and has positive effects on their behavioral adherence. Mobile apps are used to support patients’ behavioral adherence, such as in the cases of chronic kidney disease, chronic obstructive pulmonary disease, heart failure, diabetes, cancer, and post-operative management 7,10,11,1719. However, whether patients continue to use an app service depends on their satisfaction with the service 22,23.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized controlled trial in Ahmednagar, India, mothers receiving ANC reminder phone calls and SMS messages with pregnancy health information were significantly more likely than the control group to have at least four ANC visits (57.5% vs 23.5%; P < 0.0001), while facility-based delivery was high in both groups [24]. In Nigeria, a quasi-experimental study compared participants’ place of delivery with past pregnancies, and reported a greater increase in facility-based delivery in the group receiving the SMS intervention compared with the group receiving general health messages (29% vs 13%) [23]. A quasi-experimental study in rural India found that delivering IVR messages to husbands of pregnant women resulted in significantly more facility-based births in the intervention group (93.3% vs 62.1%; P < 0.001) but showed no effect on the proportion of mothers attending at least four ANC visits or consuming 100 iron folic acid tablets [35].…”
Section: Resultsmentioning
confidence: 99%